Bond graph and memristor approach to DNA analysis - Machado, J. A. Tenreiro (2016)
This paper proposes a mechanism for describing DNA information in a global perspective based on the bond graph and the memristor concepts. Present-day schemes rely upon local techniques for comparing distinct portions of DNA and, consequently, they are limited in the scope of their applicability. Systematic modeling procedures may shed an additional light toward efficient encoding algorithms, for the analysis and design of natural and artificial DNA structures.